PENGARUH PERHATIAN ORANG TUA TERHADAP KECANDUAN SMARTPHONE PADA SISWA - Rezky Permata Sari; Sri Utami; Dian Renata (Pusat Studi Gender dan Anak, IAIN Palu, 2022)
There is a tendency shown by students who cannot be separated from the grip of a smartphone. This tendency will be exacerbated if parents do not give great attention to students. This study aims to determine whether parental attention has an effect on smartphone addiction in students. This research is a quantitative research with survey type. This study was conducted at SMKS Muhammadiyah 11 Jakarta with a target population of 78 students in class X. The sample was drawn by saturated sampling so that the entire population of 78 students was used as a sample. Data were collected by using a scale technique. Data is distributed directly to students by filling in the scale. The data were then analyzed descriptively and inferentially. The categorization norm of each variable is calculated in stages with ordinal data. Inferential analysis was tested using a simple linear regression test. The results showed that: a) the level of parental attention was in the medium category, b) the level of smartphone addiction was in the medium category, and c) parental attention had a significant effect on smartphone addiction in students. Further research is needed to help minimize smartphone addiction in students.